Pengembangan Lembar Kerja Peserta Didik Berbasis Etnomatematika Terkait Kemampuan Berpikir Kreatif dan Kemandirian Belajar - Sujiarto, Heru; Mardiana, Dinny; Krisna Arya Wira Ardana (Polinomial : Jurnal Pendidikan Matematika, 2025)
This research is motivated by the results of observations that show that the learning media in the form of Student Worksheets that are available are not optimal in supporting the improvement of creative thinking skills and learning independence. This study aims to determine: (1) the validity of the ethnomathematics-based Student Worksheets related to students' creative thinking skills and learning independence; (2) the effectiveness of the ethnomathematics-based Student Worksheets on students' creative thinking skills and learning independence; and (3) the practicality of the ethnomathematics-based Student Worksheets in learning. This research is a development research with a descriptive qualitative approach consisting of three main stages, namely the preliminary research stage, development (prototyping), and assessment. The research was conducted at SMP 2 Pahlawan Toha, with data sources of 20 students, 1 material expert, 1 media expert, and 1 grade IX educator. The Student Worksheets were developed by integrating local culture (Al-Jabbar Mosque) into the geometric transformation material and using the Problem-Based Learning (PBL) approach. The results of the study showed that the Student Worksheets developed were declared valid, practical, and effective in supporting geometric transformation learning and had a positive impact on student learning independence.